The large universal Pantoea plasmid LPP-1 plays a major role in biological and ecological diversification - De Maayer Pieter; Chan Wai-Yin; Blom Jochen; Venter Stephanus N; Duffy Brion; Smits Theo H M; Coutinho Teresa A (BMC Genomics, 2012)
Abstract Background Pantoea spp. are frequently isolated from a wide range of ecological niches and have various biological roles, as plant epi- or endophytes, biocontrol agents, plant-growth promoters or as pathogens of both plant and animal hosts. This suggests that members of this genus have undergone extensive genotypic diversification. One means by which this occurs among bacteria is through the acquisition and maintenance of plasmids. Here, we have analyzed and compared the sequences of a large plasmid common to all sequenced Pantoea spp. Results and discussion The Large PantoeaPlasmids (LPP-1) of twenty strains encompassing seven different Pantoea species, including pathogens and endo-/epiphytes of a wide range of plant hosts as well as insect-associated strains, were compared. The LPP-1 plasmid sequences range in size from ~281 to 794 kb and carry between 238 and 750 protein coding sequences (CDS). A core set of 46 proteins, encompassing 2.2% of the total pan-plasmid (2,095 CDS), conserved among all LPP-1 plasmid sequences, includes those required for thiamine and pigment biosynthesis. Phylogenetic analysis reveals that these plasmids have arisen from an ancestral plasmid, which has undergone extensive diversification. Analysis of the proteins encoded on LPP-1 also showed that these plasmids contribute to a wide range of Pantoea phenotypes, including the transport and catabolism of various substrates, inorganic ion assimilation, resistance to antibiotics and heavy metals, colonization and persistence in the host and environment, pathogenesis and antibiosis. Conclusions LPP-1 is universal to all Pantoea spp. whose genomes have been sequenced to date and is derived from an ancestral plasmid. LPP-1 encodes a large array of proteins that have played a major role in the adaptation of the different Pantoea spp. to their various ecological niches and their specialization as pathogens, biocontrol agents or benign saprophytes found in many diverse environments.